A novel core–double shell heterostructure derived from a metal–organic framework for efficient HER, OER and ORR electrocatalysis. Issue 1 (5th November 2019) - Li, Jing; Li, Guangshe; Wang, Jianghao; Xue, Chenglin; Li, Xiangshuai; Wang, Shuo; Han, Bingqi; Yang, Min; Li, Liping
Abstract : A core–double shell heterostructure Co9 S8 @Co9 S8 @MoS2 -0.5 with multiple interfaces and a tunable electronic structure was constructed as an efficient tri-functional electrocatalyst. Abstract : The hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are the cornerstone reactions of renewable energy technologies, like electrochemical water splitting and metal–air batteries. To promote these reactions, robust and efficient catalysts are highly desired. However, developing multifunctional electrocatalysts for integrating the HER, OER and ORR into one electrode still remains a huge challenge. Constructing intriguing nanostructures with multiple components and hierarchical interfaces could be an efficient method to develop multifunctional electrocatalysts. Herein, we report a strategy, derived from ZIF-67, to synthesize a novel core–double shell heterostructure Co9 S8 @Co9 S8 @MoS2 -0.5 as a trifunctional pre-catalyst for the HER, OER and ORR. Firstly, a core–shell Co@Co9 S8 precursor was prepared through sulfurization and pyrolysis of ZIF-67. Then, a hydrothermal method was adopted to grow MoS2 on the Co@Co9 S8 precursor. Such a synthetic strategy endows the heterostructure with a strong interface effect that affects the electronic structure of materials and further boosts their electrocatalytic performance. The obtained Co9 S8 @Co9 S8 @MoS2 -0.5 heterostructure shows outstanding electrochemical performance. The overpotentials required for the HER and OER in an alkaline solution are 173 mV and 340 mV at 10 mA cm −2, respectively. Moreover, Co9 S8 @Co9 S8 @MoS2 -0.5 also exhibits superior ORR performance with a half-wave potential of 0.77 V. The strategy described here can be extended to a number of integrated multifunctional electrocatalysts for water splitting and metal–air batteries.